The river Ganga and its pollution- Tourists’ perception visiting Ghats of Varanasi - Sharma, Shikha; Agarwal, Madhoolika (Turizam, 2021)
The study attempts to assess tourists’ (international, national and local) perceptions for polluted state of the river Ganga in Varanasi, plausible reasons for present status and their willingness to contribute towards river cleanliness. The Kruskal-Wallis analysis suggests variation in perception for pollution and river reverence across three categories of tourists. Tourists perceived the present status of river to be dirty and urged that it can only be improved by joint efforts of people and government. Further, positive response of tourists was observed for their involvement in cleanliness drive of the river Ganga via their willingness to pay and social activities.